2016
DOI: 10.1039/c5nr08465b
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles and DNA – a powerful and growing functional combination in bionanotechnology

Abstract: Functionally integrating DNA and other nucleic acids with nanoparticles in all their different physicochemical forms has produced a rich variety of composite nanomaterials which, in many cases, display unique or augmented properties due to the synergistic activity of both components. These capabilities, in turn, are attracting greater attention from various research communities in search of new nanoscale tools for diverse applications that include (bio)sensing, labeling, targeted imaging, cellular delivery, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(122 citation statements)
references
References 582 publications
(736 reference statements)
0
121
0
1
Order By: Relevance
“…143,144 Excellent reviews on the use of DNA as templates for assembling materials by design have been reported in literature. [145][146][147][148]…”
Section: Dna Templated Nanoparticle Assembliesmentioning
confidence: 99%
“…143,144 Excellent reviews on the use of DNA as templates for assembling materials by design have been reported in literature. [145][146][147][148]…”
Section: Dna Templated Nanoparticle Assembliesmentioning
confidence: 99%
“…As a result, much efforts have devoted toward applying these nanomaterials for applications, such as sensors for environmental monitoring, food safety, point‐of‐care diagnostics, and as transducers for solar energy transfer. An equally exciting and perhaps more challenging field of application is toward their in vivo applications, including living animals and human bodies, in diverse areas, such as sensing, drug delivery, medical imaging, and cancer therapy. However, most of these nanomaterials lack selectivity toward targets of interests.…”
Section: Introductionmentioning
confidence: 99%
“…The sophisticated and elaborate systems in nature have inspired scientists to mimic the natural supramolecular assemblies to construct bioinspired and biomimetic nanomaterials. Various biomolecules including peptides, [2][3][4][5][6][7][8][9][10][11][12] proteins, [12][13][14][15] and DNA [16][17][18][19][20] have been utilized as building blocks for this purpose. Peptides in particular are ideal building blocks because of the high designability using natural and non-natural amino acids, self-assembly, and molecular recognition capability.…”
Section: Introductionmentioning
confidence: 99%